Shelf-Stable Sustainable Shrimp Thermally Processed With Reciprocal Agitation - Dixon, William R.; Watts, Evelyn G.; King, John A.; Fu, Xing; Wicker, Louise (Frontiers in Sustainable Food Systems, 2020)
Shelf stable, ready to eat shrimp offers a convenient, portion controlled option for a highly desirable seafood commodity. The perishability of shrimp requires tight cold temperature control during distribution and handling. Thermal processing of shrimp was evaluated in a multi-mode retort with automated control of come-up, heat, and cool times and with addition of high speed reciprocal agitation. Reciprocal agitation was compared to static retort for thermal process and quality parameters, including cook time, process time to achieve target lethality (F0), cook yield, texture and appearance of shelf stable shrimp. Total retort thermal processing times decreased from 30 min at 0 shakes per minute (SPM) to 17.1 min at 180 SPM to achieve same F0. The time to reach targeted F0 value of 6 min, decreased by 29%, 37%, and 42% for 45, 90, and 180 SPM, respectively, compared to static retort thermal processing. The shrimp blanch yield was about 90% and retort yield was 70 to 75% after retort thermal processing for all retort runs (0, 45, 90, and 180 SPM). Shear force texture was significantly higher at all agitation speeds compared to static retort processing with values of 384, 422 and 475 g-F with increasing agitation and 294 g-F at static conditions. Increase surface sloughing and sedimentation was observed at higher agitation speeds. Oxygen headspace was under 1% for containers flushed with nitrogen, and the rigid plastic containers used for retort packaging were not adversely affected by either static or by reciprocal agitation up to 180 SPM. Thermal processing with reciprocal agitation at 90 or 180 SPM achieves similar (p > 0.05) shear force. Reciprocal agitation at 90 SPM is recommended for improved retort efficiency and increased textural quality of retorted shrimp. A sustainable, high quality canned shrimp that can be stored at ambient temperature can be produced by reciprocal agitation retorts.